Effects of Some Water Quality Parameters Especially Total Coliform and Fecal Coliform in Surface Water of Chalakudy River. (2016) - Divya, A.H.; Solomon, P.A.
Abstract: An experimental study on surface water of Chalakudy River was conducted during Jan2013-Dec 2013 to assess the pollution load in the river due to the presence of Coliform bacteria in Chalakudy River. Physico chemical parameters of river water like pH, EC and TDS were analysed along with this microbiological analysis. Microbial contamination was detected as very high in the form of Total Coliform bacteria.